(untitled) (Revista Argentina de Cirugía, 2026)
During the SARS-CoV-2 pandemic, we observed an increase in morbidity and mortality secondary to surgical procedures. The mortality rate for elective surgery is estimated at 19.1% and is 26% for emergency procedures. Additionally, approximately half of patients who undergo surgery while infected with SARS-CoV-2 experience postoperative pulmonary complications. Due to limitations caused by the health emergency, cancer treatments in our country have been affected in terms of hospitalization capabilities and implementation of chemotherapy treatments. We report the first ALPPS (associating liver partition with portal vein ligation for staged hepatectomy) procedure performed in northeastern Argentina on a patient with multiple colorectal metastases during the SARS-CoV-2 pandemic, with successful outcomes.